Developing Independence in Early Childhood Through Full Day School - Diani, Fitri; Kurniawati Sugiyo Pranoto, Yuli (Program Studi Magister Pendidikan Anak Usia Dini, 2025)
This study explores how the full day school learning system fosters independent learning among children aged 5–6 years at Semarang Multinational School. The research involved 12 children, 4 teachers, and 8 parents from diverse family and linguistic backgrounds. Using a descriptive qualitative approach, data were collected through classroom observation, in-depth interviews, and document analysis. Findings show that the application of the International Early Years Curriculum (IEYC), which is thematic and project-based, creates meaningful, contextual learning. Children are encouraged to initiate tasks, solve problems, and complete activities independently. Teachers serve as facilitators who guide rather than instruct directly, while a child-friendly environment and consistent routines reinforce autonomy. Parental support at home further strengthens independent behavior. Challenges include varied readiness levels among children, fatigue from long school hours, and inconsistent parental involvement. This study offers practical insights for educators and curriculum planners implementing full day school models to nurture independence and character development. The findings highlight the importance of integrating structured autonomy, collaborative learning, and family-school synergy in early education settings.